Low GNG12 Expression Predicts Adverse Outcomes: A Potential Therapeutic Target for Osteosarcoma - Yuan, Jinghong; Yuan, Zhao; Ye, Aifang; Wu, Tianlong; Jia, Jingyu; Guo, Jia; Zhang, Jian; Li, Tao; Cheng, Xigao (Frontiers in Immunology, 2021)
Background: G protein subunit gamma 12 (GNG12) is observed in some types of cancer, but its role in osteosarcoma is unknown. This study hypothesized that GNG12 may be a potential biomarker and therapeutic target. We aimed to identify an association between GNG12 and osteosarcoma based on the Gene Expression Omnibus and the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) databases. Methods: Osteosarcoma samples in GSE42352 and TARGET database were selected as the test cohorts. As the external validation cohort, 78 osteosarcoma specimens from The Second Affiliated Hospital of Nanchang University were collected. Patients with osteosarcoma were divided into high and low GNG12 mRNA-expression groups; differentially expressed genes were identified as GNG12-related genes. The biological function of GNG12 was annotated using Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, gene set enrichment analysis, and immune infiltration analysis. Gene expression correlation analysis and competing endogenous RNA regulatory network construction was used to determine potential biological regulatory relationships of GNG12. Overall survival, Kaplan-Meier analysis, and log-rank tests were calculated to determine GNG12 reliability in predicting survival prognosis. Results: GNG12 expression decreased in osteosarcoma samples. GNG12 was a highly effective biomarker for osteosarcoma (area under the receiver operating characteristic [ROC] curve [AUC] = 0.920) and the results of our Kaplan-Meier analysis indicated that overall survival and progression free survival differed significantly between low and high GNG-expression group (P < 0.05). Functional analyses indicated that GNG12 may promote osteosarcoma through regulating the endoplasmic reticulum. Expression correlation analysis and competing endogenous RNA network construction showed that HOTTIP/miR-27a-3p may regulate GNG12 expression. Furthermore, the subunit suppresses adaptive immunity via inhibiting M1 and M2 macrophage infiltration. GNG12 was inhibited in metastatic osteosarcoma compared with non-metastatic osteosarcoma, and its expression predicted survival of patients (1-year, 3-year, and 5-year AUCs were 0.961, 0.826, and 0.808, respectively). Conclusion: This study identified GNG12 as a potential biomarker for osteosarcoma prognosis, highlighting its potential as an immunotherapy target.